Social Justice: The Basis for Implementing Compensation in Land Acquisition for The National Strategic Projects in Indonesia - Fahrul Fauzi (Pusat Penelitian dan Pengabdian kepada Masyarakat, Sekolah Tinggi Pertanahan Nasional, 2021)
Abstract: Infrastructure development with the National Strategic Project program must still pay attention to the concept of social justice. The land is the primary indicator needed in this development. Conflicts often occur between landowning communities and the government to acquire land for the National Strategic Projects. The issue of compensation that does not meet the point of agreement is the main problem in land acquisition. This article examines how the concept of social justice is laid as the basis for implementing compensation in land acquisition for National Strategic Projects in Indonesia. This article's writing is supported by the juridical-normative research method with a statutory regulation approach and a conceptual approach. In the concept of social justice, it is permissible to ask for sacrifices in the public interest, but it cannot be justified that these sacrifices are first requested from people who are already disadvantaged in society, so the government must consider several aspects before implementing land acquisition so that it does not harm the community and remain following the concept of social justice. Keywords: Social Justice, Land Acquisition, Compensation, the National Strategic Project. Intisari: Pembangunan infrastruktur melalui Proyek Strategis Nasional harus tetap memperhatikan konsep keadilan sosial. Tanah merupakan indikator utama yang dibutuhkan dalam pembangunan tersebut. Konflik sering terjadi antara masyarakat pemilik tanah dan pemerintah dalam rangka pengadaan tanah untuk kepentingan Proyek Strategis Nasional. Masalah ganti rugi yang tidak menemui titik kesepakatan menjadi masalah utama dalam hal pengadaan tanah. Artikel ini mengulas bagaimana konsep keadilan sosial diletakkan sebagai dasar pelaksanaan ganti kerugian dalam pengadaan tanah untuk Proyek Strategis Nasional di Indonesia. Penulisan artikel ini didukung dengan metode penelitian yuridis-normatif dengan pendekatan peraturan perundang-undangan dan pendekatan konsep. Dalam konsep keadilan sosial memang boleh untuk diminta pengorbanan demi kepentingan umum, namun tidak dapat dibenarkan bahwa pengorbanan ini pertama-tama diminta dari orang-orang yang sudah kurang beruntung dalam masyarakat, sehingga pemerintah harus mempertimbangkan beberapa aspek sebelum pelaksanaan pengadaan tanah sehingga tidak merugikan masyarakat dan tetap sesuai dengan konsep keadilan sosial. Kata Kunci: Keadilan Sosial, Pengadaan Tanah, Ganti Rugi, Proyek Strategis Nasional.